Condition of Service and Preschool Teachers’ Productivity in Public Preschools in Rivers State - Ukashia, Joseph Ogar; Joshua, Kpoabari Amos (International Journal on Integrated Education, 2023)
The productivity of preschool teachers is the reason for children development and learning in school. The dearth of motivation of preschool teachers is suicidal to the overall performance of the caregiver in the school. Observation reveal that despite the efforts of government in ensuring that preschool teachers are motivated, it seems there is still more to do on the part of education stakeholders in ensuring that preschool teachers become productive in Rivers State. This study therefore investigated Condition of service and preschool teachers’ productivity in Public preschool in Rivers State. The correlational Research design was adopted. Two purposes were posed, two research questions were raised and answered and two hypotheses were tested in the study. 6,572 subjects (6000 preschool teachers and 572 head-teachers) found in 572 Public Preschool in Rivers State constitute the population for the study out of which 708 subjects (649 preschool teachers and 59 head-teacher) representing approximately 10.78% of the entire population was sampled for the study using Stratified Sampling Technique. Study employed the correlational research design. The research instruments used for data collection are the researcher-developed checklist and a questionnaire. Reliability index of 0.73 was determined through a test-retest method which was used to adjudge the instruments reliable. The instrument was administered to Preschool teachers in public preschool in Rivers State. Mean and Standard Deviation was used to answer the research questions, while Pearson Product Moment Correlation (PPMC) was used to test the null hypotheses at 0.05 level of significance. The finding revealed that there is a significant relationship between professional development and productivity of preschool teachers in public preschool in Rivers State, there is a significant relationship between work load and productivity of preschool teachers in public preschool in Rivers State.